The level of air pollution in the impact zone of coal-fired power plant (Karaganda City) using the data of geochemical snow survey (Republic of Kazakhstan); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Adil'bayeva Т. E.; Talovskaya A. V. Anna Valerievna; Yazikov Y. G. Yegor (Egor) Grigoryevich; Matveenko I. A. Irina Alekseevna (Geoecology and Environmental Protection, 2016)
Title screen